Design and analysis of a high‐integration and low‐loss bearingless flywheel motor in vehicle. Issue 10 (22nd April 2021) - Yang, Fan; Yuan, Ye; Meng, Gaojun; Yan, Libin
Abstract: This study investigates an outer rotor bearingless flywheel motor for flywheel batteries in vehicle that exhibits the advantages of high integration and low loss due to outer rotor direct‐drive and bearingless technologies. A hybrid excitation outer rotor bearingless flywheel motor with four‐degrees‐of‐freedom radial suspension and permanent magnet bias is also proposed, further improving the advantages of high integration and low loss. In addition, suspension force density is ameliorated and suspension–torque coupling is reduced through structure design. To verify the aforementioned advantages of hybrid excitation outer rotor bearingless flywheel motor, its working principles are introduced and its electromagnetic characteristics are analyzed using the finite element method. Comparisons with 12/8 ORBFM are also conducted by focusing on suspension loss and suspension force density.